2016
DOI: 10.21451/1984-3143-ar745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different feeding schedules on egg quality, blood, and bone parameters in broiler breeders

Abstract: The aim of this study was to evaluate different feeding schedules and their relationship to calcium (Ca) and phosphorus (P) plasma levels and egg quality of broiler breeders. The feeding schedules were: single feeding at 8:00 AM; twice daily feeding (50% at 8:00 AM and 50% at 3:00 PM) and single feeding at 3:00 PM. 330 female and 45 male Cobb 500 broiler breeders were used from 40 to 60 weeks of age. The experimental design was completely randomized, consisting of 3 treatments with 5 replicates each, with 22 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…This agreed with the report of Hall, ( 2005) who reported that the medullary bone calcium can be deposited and released in response to changes in calcium supply and demand during eggshell formation and that only an average of 4grams of calcium is required in a diet to maintain good shell quality. However, the report in this study contradicted the report of Londero et al, (2016) who reported that the practice of feeding only once a day cannot supply the nutritional need of hen, particularly for eggshell formation. The contradiction might be as a result of the different breed used for the trials.…”
Section: Discussioncontrasting
confidence: 99%
“…This agreed with the report of Hall, ( 2005) who reported that the medullary bone calcium can be deposited and released in response to changes in calcium supply and demand during eggshell formation and that only an average of 4grams of calcium is required in a diet to maintain good shell quality. However, the report in this study contradicted the report of Londero et al, (2016) who reported that the practice of feeding only once a day cannot supply the nutritional need of hen, particularly for eggshell formation. The contradiction might be as a result of the different breed used for the trials.…”
Section: Discussioncontrasting
confidence: 99%
“…As far as the commercial layer is concerned, split feeding strategies in organic farming (van Krimpen et al 2018) and aviary system (Molnár et al 2018) did not affect egg production. Twice a day feeding system did not also affect the egg weight of commercial layers (Samara et al 1996;Backhouse and Gous 2005;Soltanmoradi et al 2013;Londero et al 2015Londero et al , 2016. However, the other studies on breeders claim the contrary findings in which twice a day feeding strategy positively influenced the egg weight (Spradley et al 2008;Taherkhani et al 2010;Moradi et al 2013).…”
Section: Effect Of Dietary Strategies On Bird's Production Performancementioning
confidence: 69%
“…However, on the other hand, improvement in egg production while feeding a standard diet twice a day has also been observed (Taherkhani et al 2010;Moradi et al 2013;Soltanmoradi et al 2013). Overall reviewing the previous studies, the older literature explained that twice a day feeding strategy did not alter the egg production except (Londero et al 2015(Londero et al , 2016, while the recent studies (onward from 2008) showed higher egg production in breeders fed twice a day. This inconsistency between different studies might be caused by their genetic differences explained by (van Emous and Mens 2021).…”
Section: Effect Of Dietary Strategies On Bird's Production Performancementioning
confidence: 80%
See 1 more Smart Citation